The toxicity of a crude enzyme extract from Gliomastix murorum in Swiss Albino mice. - Aritajat S. (2014)
A crude enzyme extract from a fungus, Gliomastix murorum, could be used in the synthesis of oligosaccharides that are essential to the food and drug industries. This extract may contaminate such products and lead to serious health problems. An investigation on the possible toxicity and mutagenic effect of the extract from this fungal isolate was carried out in Swiss Albino mice. One hundred and 50% of the crude enzyme extract were injected intraperitoneally into the mice every 2 days for 30 days. Normal saline (0.9%), cultivation medium, and cyclophosphamide (80 mg/kg body weight) were given to the control groups. The results indicated that the white blood cell count, serum creatinine, and uric acid of the treated mice were significantly higher than those of the controls (p<0.05), whereas the serum urea-N was lower. For the micronucleus test, mice treated with the extract, especially the group received 100% crude enzyme extract, showed a higher number of micronuclei in polychromatic erythrocytes, as compared to controls. Nevertheless, the micronucleus values were not as high as those found in mice treated with cyclophosphamide, the mutagenic agent. It can be concluded from the results that crude enzyme extract had minor toxic effects on various organ systems tested; more extensive investigation on the safe use of this extract is therefore necessary.